2022
DOI: 10.29261/pakvetj/2022.060
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiological Investigation of Cryptosporidium sp., Giardia duodenalis, Enterocytozoon bieneusi and Blastocystis sp. Infection in Free-ranged Yaks and Tibetan Pigs on the Plateau

Abstract: Intestinal parasites are of great economic importance in livestock. However, scarcity of data has been found about the prevalence of four important intestinal parasites including Cryptosporidium sp., Giardia duodenalis, Enterocytozoon bieneusi and Blastocystis sp. infection in free-ranged yaks and Tibetan pigs during the winter season on the plateau. Fecal samples of yaks (n=40) and Tibetan pigs (n=60) were collected and molecular identification of these parasites was performed through nested PCR amplification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the United States, calf deaths due to diarrhea account for 56.4% of pre-weaned dairy deaths [ 10 ]. Diarrhea is associated with various kinds of infectious and non-infectious etiological factors [ 11 ]. Various practices, including herd management, better nursing, feeding, nutrition, and utilization of biopharmaceuticals are implemented, but it is still an immense challenge to figure out diarrhea in calves [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, calf deaths due to diarrhea account for 56.4% of pre-weaned dairy deaths [ 10 ]. Diarrhea is associated with various kinds of infectious and non-infectious etiological factors [ 11 ]. Various practices, including herd management, better nursing, feeding, nutrition, and utilization of biopharmaceuticals are implemented, but it is still an immense challenge to figure out diarrhea in calves [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that intestinal epithelial cells are mainly composed of absorptive cells, goblet cells, paneth cells, and endocrine cells [ 39 ]. These cells are constantly renewed to ensure the integrity of the intestinal epithelium and maintain the normal function of the intestinal mucosal barrier [ 40 ]. Goblet cells are the major secretory cells of the GI tract.…”
Section: Discussionmentioning
confidence: 99%